Kelompok Swabantu Diabetes Terhadap Pengetahuan Dan Kepatuhan Kontrol Pasien Diabetes Mellitus - I Made Mertha; I Nyoman Ribek; I Made Widastra (Jurnal Gema Keperawatan, 2016)
The research objective is to identify diabetes self-help groups, self helpkompok analyze the effect of diabetes on patients' knowledge of DM, and analyze the influence of self-help groups for compliance control diabetes patients with diabetes mellitus. This study is quasy-experimental with pre-post design without control group. The study was conducted at the health center IV South Denpasar for 5 months ie from June to October 2015. The study population was patients with DM and DM patients at high risk who went to the health center IV South Denpasar. Samples were selected that met the inclusion criteria and exclusion amounts to 35 people. Respondents subsequently formed self-help groups. Self-help groups in the form of counseling treatment diabetes management, prevention of the risk of diabetes, foot care, foot gymnastics, yoga activities and random blood sugar  measurements once a month. Data collection tool was a questionnaire about their knowledge and compliance controls are carried out pre and post treatment. Based on the results of statistical tests revealed no influence of self-help groups for knowledge and compliance control of diabetic patientsat the health center IV South Denpasar (p = 0.000; α = 0.05).